INSERSI NILAI ISLAMI DALAM MATA PELAJARAN GEOGRAFI PADA SISWA KELAS XI IIS SMA NEGERI 1 PADANG - Fitrianingsih, Nisa; Anwar, Syafri (JURNAL BUANA, 2024)
This study aims to determine the teacher's preparation and planning in making learning programs and to find out the application of Islamic values insertion in Geography subjects at SMAN 1 Padang. This type of research is descriptive qualitative. The research subject was a geography teacher who taught in class XI IIS 1 SMAN 1 Padang. Methods of data collection by observation, interviews, and document analysis. Data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The validity of the data using triangulation of sources and techniques. The results showed that: At the planning stage, the teacher included Islamic values in the objectives and preliminary activities, but the teacher inserted religious values several times in the PBM. In the implementation of learning, the insertion of religious values is applied to good relations with God, good relations with fellow human beings and good relations with nature